IMPROVING THE VACCINATION RATES FOR IMMUNOSUPPRESSED PATIENTS WITH INFLAMMATORY BOWEL DISEASE. (22nd January 2022) - Cheng, Tony; Kreitman, Kyle; Stowe, Carissa; Waters, Bradford; Baidoo, Leonard
Abstract: BACKGROUND: Immunosuppressive therapy (IS) has altered the course of Inflammatory Bowel Disease (IBD). IBD patients are at considerable risk of developing vaccine-preventable illness and are even more susceptible when on treatment. Many of these patients fail to receive appropriate vaccinations for influenza, pneumonia, hepatitis B, Shingles and recently COVID. Our aim was to develop a quality improvement intervention to increase recommended vaccinations in IBD patients on IS. METHODS: A retrospective chart analysis was completed at the Memphis Veteran Affairs Gastroenterology Practice. 55 patients were found to be on immunosuppressive therapy with a biologic and/or immunomodulator. Once identified, these patient's vaccination records were reviewed to see if they were up to date on recommended vaccinations for influenza, pneumonia, hepatitis B, COVID, and Shingles. Patients who were not up to date on their vaccinations were called by a provider (Resident, Fellow, or Nurse Practitioner), and were offered a nurse visit to be given the appropriate vaccinations. After a 6-month intervention period, the data on the 55 patients was recollected and analyzed. RESULTS: Of the patients analyzed, 63% (n=35) had Crohn's disease and 37% (n=20) had Ulcerative Colitis. The most common biologic medication the patients were on was adalimumab (n=24), and the most common immunomodulator was azathioprine (n=17). Prior to the intervention, 22% had received the shingles vaccine, 20% had received the COVID-19 vaccine, 78% had received the hepatitis B vaccine, 69% had received the flu vaccine, 62% had received the pneumococcal 23 vaccine, and 72% had received the pneumococcal 13 vaccine. After the intervention, 65% had received the shingles vaccine, 65% had received the COVID-19 vaccine, 87% had received the hepatitis B vaccine, 85% had received the flu vaccine, 78% had received the pneumococcal 23 vaccine, and 84% had received the pneumococcal 13 vaccine. CONCLUSION: Patients on immunosuppressive therapy remain vulnerable to vaccine-preventable illnesses such as Shingles, Pneumococcal Pneumonia, Influenza, Hepatitis B, and COVID-19. Our quality improvement intervention increased overall vaccination adherence. This project was a proof of concept and in the future, we hope to integrate a warning system into our practice to alert providers when these patients are due for their appropriate vaccinations. It is also a practice that can be adopted by other healthcare providers who treat patients with IS and biologics to improve vaccination uptake.